Unshielded facility testbed for electromagnetic wave attenuation using absorber slabs - Chang-Hee Hyoung; Jung-Hwan Hwang; Jong Hwa Kwon (ETRI Journal)
This paper presents a testbed for unshielded facilities utilizing planar electro-magnetic absorbers. These slabs demonstrate comparable shielding effective-ness to that of reinforced concrete in the frequency range from 1 GHz to6 GHz. The testbed serves as a platform for developing a measurement methodto assess unshielded facilities. It can be configured with different materials thathave various levels of shielding effectiveness. We evaluate the shielding effec-tiveness of the absorber slab and extract its electromagnetic parameters. Thetestbed is implemented in a semi-anechoic chamber with inner dimensions of3.00 3.06 2.50 m 3 . The electromagnetic wave attenuation for theunshielded facilities is defined as the ratio of received power within the assess-ment space relative to the incident power. The measurement results providequantitative information on the attenuation of electromagnetic waves withinunshielded facilities. The testbed configured with two types of incident planesis evaluated and compared with the mean attenuation and distributioncharacteristics